PENGARUH PENGGUNAAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SD - Fadhillah Muhibbah; Khairil Iba (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses a study that aims to determine the effect of animated video media on mathematics learning outcomes for fourth-grade students at SDN Dukuh 09 Pagi. The research refers to a quantitative approach. The type of research method used was quasi- experimental research with a post-test-only control group design. In this design, it involved two classes, class IV A as a control class with 32 students and class IV B as an experimental class with 32 students. The data collection process was carried out by providing a post-test to the two classes. To determine the results of the study, it was used the T-Test formula. The determination was Ho rejected if Tcount > Ttable and Ho accepted if Tcount < Ttable. The test results of the research indicated that Tcount was 7.391 and Ttable was 1.999 with a significant level (a)0.05. Because Tcount > Ttable was 7,391 > 1,999, therefore, it could be concluded that there was an effect of animated video media on mathematics learning outcomes for fourth-grade students.